Sustainability dimensions in enhancing the energy and resource efficiency of big data systems - D/O Arunachalam, Aishwharya Raani; Jusoh, Yusmadi Yah; Abdullah, Rusli; Umarova, Zhanat; Akhmetova, Sabira; Iztayev, Zhalgasbek; Zhumatayev, Nurlybek (Institute of Advanced Engineering and Science, 2024)
Big data systems are essential for many businesses to grow, leveraging the vast amounts of data they generate and access. However, big data systems are plagued by significant sustainability challenges. Thus, this study aims to identify metrics that can measure the sustainability of big data systems. This research conducted a comprehensive literature review to identify five key sustainability dimensions: technical, environmental, economic, social, and individual. Then, a set of 29 metrics corresponding to these dimensions was developed. To ensure the relevance and applicability of these metrics, an expert validation session was carried out with five experts in the big data field. The validation process confirmed the appropriateness of our proposed metrics and modification take place. The findings of this study present 30 metrics upon experts’ validation that could enhance the sustainability of big data systems, offering meaningful insights for researchers and practitioners aiming to enhance resource and energy efficiency in this domain.